Dimeric and Trimeric Hydrolyzable Tannins from Quercus coccifera and Quercus suber - Ito, Hideyuki; Yamaguchi, Koji; Kim, Tae-Hoon; Khennouf, Seddik; Gharzouli, Kamel; Yoshida, Takashi (Journal of Natural Products, 2002)
Three new hydrolyzable tannins, cocciferins D1 (1), D2 (2), and T1 (4), were isolated from the leaves of Quercus coccifera. Cocciferin D2 (2) and two additional new tannins, cocciferins D3 (3) and T2 (5), were also obtained from the leaves of Quercus suber. Their oligomeric structures were elucidated on the basis of spectroscopic methods and chemical evidence. Compounds 2, 3, and 5 were rare oligomers possessing glucose cores with both open-chain and pyranose forms.
doi: 10.1021/np010465i
Keywords: NMR; Quercus coccifera; Quercus suber; structure (voyant); Tannins

Composition of Suberin Extracted upon Gradual Alkaline Methanolysis of Quercus suber L. Cork - Lopes, Marta H.; Gil, Ana M.; Silvestre, Armando J. D.; Neto, Carlos Pascoal (Journal of Agricultural and Food Chemistry, 2000)
The monomeric composition of suberin extracts obtained by gradual alkaline methanolysis of Quercus suber cork was determined by gas chromatography?mass spectrometry (GC-MS). Results show that 1-alkanols and alkanoic and α,?-alkanedioic acids are preferentially removed upon mild alkaline conditions, whereas mid-chain-modified ?-hydroxyalkanoic acids are preferentially removed under stronger alkaline conditions. Saturated ?-hydroxyalkanoic acids are found to be abundant in all suberin extracts. These results are consistent with two distinct suberin fractions with different locations in cork cell walls and/or esterification degrees. It is proposed that these fractions correlate with the two main suberin peaks in the solid state 13C NMR spectra of cork and suberin extracts. Quantitative GC-MS analysis showed that suberin monomers comprise ?30% (w/w) of the suberin extracts, the remaining comprising nonvolatile structures with high Mn values, as measured by vapor pressure osmometry. The presence of a large fraction of high molecular weight aliphatic structures in suberin extracts is supported by the corresponding NMR spectra. Keywords: Suberin; cork; Quercus suber L.; GC-MS; NMR; alkaline methanolysis
doi: 10.1021/jf9909398doi: 10.1021/jf9909398The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Alkaline methanolysis; Cork; GC-MS; NMR; Quercus suber L.; suberin

A 13C solid state nuclear magnetic resonance spectroscopic study of cork cell wall structure: the effect of suberin removal. - Gil, A M; Lopes, M; Rocha, J; Pascoal Neto, C (International journal of biological macromolecules, 1997)
Solid state 13C NMR measurements of cork, before and after suberin removal, showed that aliphatic suberin is spatially separated from carbohydrate and lignin and experiences higher motional freedom. Two types of chain methylenes, differing in chemical shift and in dynamic properties, were identified in aliphatic suberin. Experimental evidence indicated that the more motionally hindered methylenes are those situated nearer the linkages of aliphatic suberin to the cell wall. These linkages were shown to involve -CH2O- groups, probably engaged in ester linkages to phenylpropane units and carbohydrate C6 carbons. Spectral intensity changes indicated that, during the first steps of alkaline desuberization, these linkages are broken and the shorter aliphatic suberin chains removed. Longer chains require hydrolysis of the ester linkages within the chains and are removed upon stronger alkaline treatment. T1(C), T1 rho (H) and T1 rho (C) relaxation times have shown that the removal of suberin from cork leads to a motionally restricted and more compact environment, on the megahertz and mid-kilohertz timescales. The properties of cork suberin showed that suberin organization in cork is distinct from that in potato tissue.
Keywords: Cork; NMR; Quercus suber; suberin

Betulin-3-Caffeate from Quercus suber, 13C-nmr Spectra of Some Lupenes - Patra, Amarendra; Chaudhuri, Swapan K; Panda, Samir K (Journal of Natural Products, 1988)
A new a-lupene ester, Iup-20(29)-en-28-01-3P-y1 caffeate (betulin-3-caf- feate) El], has been isolated from cork waste along with betulin, betulonic acid, and betulinic acid. "C-nrnr signal assignments of 1 and its derivatives are reported
doi: 10.1021/np50056a004
Keywords: a-lupene derivatives; Chemical characterization (voyant); Cork waste; NMR; Structural characterization

Structural studies of a hemicellulose B fraction from the cork of Quercus suber - Asensio, Amparo (Carbohydrate Research, 1987)
Polysaccharide B-2 contains xylose, arabinose, glucose, galactose, 4-0-methylglucuronic acid, and rhamnose in the molar ratio of 17: 12: 12:6:4: 1. The polysaccharide has a backbone of P(1-4)- and P( 1-3)-linked glucopyranosyl, P(lk4)-linked xylopyranosyl, and (1-4)- and (1-6)-linked galactopyranosyl residues. Arabinofuranosyl, rhamnopyranosyl, and some xylopyranosyl and galactopyranosyl groups are present as nonreducing end units. Glucopyranosyluronic acid side chains are attached at 0-2 of some xylose residues. The anomeric configurations of the different glycosyl groups were determined by a study of the chromium trioxide oxidation of the acetylatcd polysaccharide and by nuclear magnetic reasonance spectra of the methylated polysaccharide.
PGPG
Keywords: acid hydrolysis; chromium trioxide oxidation; methylation analysis; NMR; Polysaccharide B-2; Structural analysis